Glomus mosseae improved the adaptability of alfalfa (Medicago sativa L.) to the coexistence of cadmium-polluted soils and elevated air temperature - Gao, Yun-feng; Jia, Xia; Zhao, Yong-hua; Ding, Xiao-yi; Zhang, Chun-yan; Feng, Xiao-juan (Frontiers in Plant Science, 2023)
The coexistence of heavy metal-polluted soils and global warming poses serious threats to plants. Many studies indicate that arbuscular mycorrhizal fungi (AMF) can enhance the resistance of plants to adverse environments such as heavy metals and high temperature. However, few studies are carried out to explore the regulation of AMF on the adaptability of plants to the coexistence of heavy metals and elevated temperature (ET). Here, we investigated the regulation of Glomus mosseae on the adaptability of alfalfa (Medicago sativa L.) to the coexistence of cadmium (Cd)-polluted soils and ET. G. mosseae significantly enhanced total chlorophyll and carbon (C) content in the shoots by 15.6% and 3.0%, respectively, and Cd, nitrogen (N), and phosphorus (P) uptake by the roots by 63.3%, 28.0%, and 85.2%, respectively, under Cd + ET. G. mosseae significantly increased ascorbate peroxidase activity, peroxidase (POD) gene expression, and soluble proteins content in the shoots by 13.4%, 130.3%, and 33.8%, respectively, and significantly decreased ascorbic acid (AsA), phytochelatins (PCs), and malondialdehyde (MDA) contents by 7.4%, 23.2%, and 6.5%, respectively, under ET + Cd. Additionally, G. mosseae colonization led to significant increases in POD (13.0%) and catalase (46.5%) activities, Cu/Zn-superoxide dismutase gene expression (33.5%), and MDA (6.6%), glutathione (22.2%), AsA (10.3%), cysteine (101.0%), PCs (13.8%), soluble sugars (17.5%), and proteins (43.4%) contents in the roots and carotenoids (23.2%) in shoots under ET + Cd. Cadmium, C, N and chlorophyll significantly influenced shoots defenses and Cd, C, N, P, and sulfurS significantly affected root defenses. In conclusion, G. mosseae obviously improved the defense capacity of alfalfa under ET + Cd. The results could improve our understanding of the regulation of AMF on the adaptability of plants to the coexistence of heavy metals and global warming and phytoremedization of heavy metal-polluted sites under global warming scenarios.